Experiencing information seeking and learning: a study of the interaction between two phenomena - Louise Limberg (Information Research: An International Electronic Journal, 1999)
Reports the design and findings of a research project for a doctoral thesis on information seeking and use in a learning context. Theoretical frames were found in LIS use and user studies and in phenomenographic learning theory. The empirical study was conducted in a naturalistic setting with a group of 25 high school seniors. Phenomenographic method, designed to investigate variation in people's ways of experiencing phenomena in the world, was used. Three major ways of experiencing information seeking and use were identified; (a) fact-finding, (b) balancing information in order to make correct choices, (c) scrutinizing and analysing. The variation in information seeking and use interacted closely with variation in learning outcomes. These findings form a basis for further research on variation in users' ways of experiencing the content of information. They also provide a basis for didactic development of information literacy instruction.